2020
DOI: 10.1111/jcmm.15137
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tregs as a cell‐based therapy via CD39 for benign prostate hyperplasia with inflammation

Abstract: Benign prostatic hyperplasia (BPH) occurs most commonly among older men, often accompanied by chronic tissue inflammation. Although its aetiology remains unclear, autoimmune dysregulation may contribute to BPH. Regulatory T cells (Tregs) prevent autoimmune responses and maintain immune homeostasis. In this study, we aimed to investigate Tregs frequency, phenotype, and function in BPH patients and to evaluate adoptive transfer Tregs for immunotherapy in mice with BPH via CD39. Prostate specimens and peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…found that NK cells expressing the ectonucleotidases, CD73, produced more IL-10 and TGF-β via STAT3 transcriptional activity ( 37 ). In addition, CD39+ Tregs secreted more IL-10 and TGF-β to inhibit inflammation ( 38 ). These data indicated that CD38+CD39+ NK cells expressed more IL-10 and TGF-β for immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…found that NK cells expressing the ectonucleotidases, CD73, produced more IL-10 and TGF-β via STAT3 transcriptional activity ( 37 ). In addition, CD39+ Tregs secreted more IL-10 and TGF-β to inhibit inflammation ( 38 ). These data indicated that CD38+CD39+ NK cells expressed more IL-10 and TGF-β for immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Davidsson et al have reported increased number of stromal CD4 + Tregs in patients with post-atrophic hyperplasia and prostate cancer (26). Jin et al detected low Treg cell count in peripheral blood taken from BPH patients, but they found high Treg infiltration in prostate tissue with mild or moderate inflammation (13). They also found that Treg cells almost disappeared in severely inflamed prostate tissue, and suggested that this inconsistency was caused by the use of different patient samples (13).…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al detected low Treg cell count in peripheral blood taken from BPH patients, but they found high Treg infiltration in prostate tissue with mild or moderate inflammation (13). They also found that Treg cells almost disappeared in severely inflamed prostate tissue, and suggested that this inconsistency was caused by the use of different patient samples (13). The transcription factor called FOXP3 controls the Treg cell system and is the most specific marker of these cells (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD39 + Tregs present stronger stability and function under inflammatory conditions ( 23 ). The role of CD39 on Tregs in limiting tissue injury has been studied in myocardial infarction ( 24 ) and benign prostate hyperplasia ( 25 ). All of these findings suggest a potential role of CD39 + Tregs in acute lung inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%